Sedentary lifestyle and body weight status among youth at public secondary schools in Selangor - Ali Mansor, Amiraa; Abdullah, Haslinda; Azman, Adibah (Human Resource Management Academic Research Society, 2017)
Background: Prior research indicates that youth are more at risks for developing obesity, where obesity are associated with several health complications as well as significant healthcare costs. Malaysia has been categorised as the fattest country in South-East Asia with its obesity rates are alarming and on the rise. Aim: To determine the level of body weight status and sedentary behaviour among youth at public secondary schools in Selangor. Methods: Data were obtained through a cross sectional study where questionnaires were distributed to students aged 16 years old through cluster sampling method. After data was cleaned and prepared for the statistical analysis, the sample was reduced to 385 students: 195 female and 190 male. Body Mass Index (BMI) and Sedentary Behaviours Questionnaires adapted from Project EAT II were used to assess inactive lifestyle. Results: It indicates in which n=115 of respondents were on the worrying categories either overweight, obese type I, obese type II or obese type III. Meanwhile, the inactive duration for majority of the respondents due to sedentary lifestyle were calculated as 5 hours per day.